Water Quality of Marshyangdi River, Nepal: An Assessment Using Water Quaity Index (WQI) - Singh, Reeta; Kayastha, Sadhana Pradhanang; Pandey, Vishnu Prasad (Journal of Institute of Science and Technology, 2021)
Water quality index (WQI) is a valuable arithmetic tool that depicts the overall status of water quality in a single number to prioritize for management interventions. This study aims to assess water quality based on the WQI to provide insights into the status of the aquatic ecosystems in the Marshyangdi River basin, a tributary of the Narayani River, originating from the Himalaya. Water samples were collected from twenty-one sampling locations in the Marshyangdi River covering four districts from upstream (Kangsar) to the downstream region (Mugling) during pre-monsoon season (May) 2019. Eight selected physico-chemical parameters (TDS, pH, EC, DO, Cl-, NH3, PO43-, NO3-) were analyzed and aggregated in the form of WQI. Results showed that WQI ranges from 32.5 to 46.9, indicating the excellent water quality suitable for the sustenance of the aquatic ecosystem at all the sampling locations. These study results are expected to provide the baseline information on the present status of water quality along the longitudinal section of the Marshyangdi River, which could be helpful for the concerned authorities to manage water quality for the sustenance of the aquatic ecosystem.